The Influence of Halal Certification and Religiosity on Interest in Buying Mixue Products Through Attitude as an Intervening Variable (Study of Communities in Madiun City) - Sidanti, Heny; Asmike, Metik; Mohammad Mahfudz Alkarimy, Noor (International Journal of Science, Technology & Management, 2023)
The processed food industry is one of the industries that has been able to survive and grow positively, even including the one with the highest growth. The processed food industry as part of manufacturing has very promising prospects, both globally and domestically. Several factors determine interest in purchasing food products, including halal certification and religiosity. This study aims to empirically prove the effect of halal certification and religiosity on purchasing interest in mix products through attitude as an intervening variable.This type of research is descriptive quantitative. Data collection was carried out by distributing questionnaires. The sampling method used is purposive sampling method. The sample in this study is the community in Madiun City. The data used in this research is primary data. Regarding data analysis using multiple linear regression analysis with the help of the SPSS version 19 program. The results of this study prove that the variables of halal certification and religiosity have a positive and significant effect on the intention to buy mixed products. The results of this study also show that the variables of halal certification and religiosity affect consumer attitudes.